Analysis Of Policy Implementation Of The Service Of Youth And Sports In An Effort To Increasing Athletes Achievement In Bengkulu Province - Heru Purnawan; Henny Aprianty; Diky Mariantoy; Dodo Sutardi; Rahiman Dani (GAYAKU PUBLISHER, 2022)
The implementation of the Youth and Sports Service's policy regarding the development of achievement sports human resources is the basis for every sports actor to improve his performance. Improvement of sports achievements which have the duties and functions contained in the Bengkulu Governor Regulation Number 43 of 2016 concerning the Position, Organizational Structure of Duties and Functions as well as the work procedures of the Youth and Sports Office. The purpose of this study was to determine the implementation of policies and to understand the obstacles faced in implementing the policies of the Department of Youth and Sports in an effort to improve the achievements of Bengkulu Province athletes. The method used is descriptive qualitative with research subjects Analysis of Youth and Sports Service Policy Implementation about improving athlete achievement. The population in this study found 9 people. The sources of data in this study are documents on sports policy, observations, and interviews with the Head of the Youth and Sports Office, Head of Youth Development, Head of Sports Achievement Improvement, Head of UPTD Management and Development of Youth and Sports Facilities and Infrastructure (P2SPKK), Chairperson General KONI Bengkulu, and athletes. The results showed that the implementation of the Youth and Sports Office policy was good with training programs and giving rewards but running optimally. The obstacles to efforts to improve athlete achievement were seen by the lack of budget provided, lack of support from the sports industry in improving athlete achievement and facilities and infrastructure. insufficient exercise.